LINEZOLID INDUCED BLACK HAIRY TONGUE: A RARE SIDE EFFECT - Aijazi, Ishma; Abdulla, Fadhil M (Journal of Ayub Medical College Abbottabad, 2014)
Linezolid induced black hairy tongue is a rare benign reversible side effect of linezolid therapy. We report a case of a 61 year old diabetic lady who developed thrombocytopenia and black hairy discoloration of the tongue after being prescribed linezolid for foot osteomyelitis by the orthopaedic surgeon. Patient was encouraged to practice good oral dental hygiene, advised to use a soft tooth brush, regular mouth wash and baking soda containing tooth paste. The condition resolved four weeks after cessation of the antibiotic therapy. Keywords: Linezolid, side effect, black tongue, oxazolidinone